Environmental Problems Observed In Our Society Today And Their Prevention Issuies - Atajanova Muyassar Atajanovna (Genius Journals, 2024)
This article describes the environmental problems arising in our society today and the reasons for their occurrence. The ongoing work to prevent environmental problems is analyzed in detail.
Keywords: Ecological culture; upbringing; environment